Toxicological study of the degradation products of antineoplastic agent etoposide in commercial formulation treated by heterogeneous photocatalysis using SrSnO3 - de Sousa Filho, Idio Alves; Lobo, Tatiane Martins; Grisolia, Cesar Koppe; Weber, Ingrid Távora; Osugi, Marly Eiko [UNESP] (Springer Nature, 2018)
Etoposide is an antineoplastic agent used for treating lung cancer, testicular cancer, breast cancer, pediatric cancers, and lymphomas. It is a pollutant due to its mutagenic and carcinogenic potential. Disposal of waste from this drug is still insufficiently safe, and there is no appropriate waste treatment. Therefore, it is important to use advanced oxidative processes (AOPs) for the treatment and disposal of medicines like this. The use of strontium stannate (SrSnO3) as a catalyst in heterogeneous photocatalysis reactions has emerged as an alternative for the removal of organic pollutants. In our study, SrSnO3 was synthesized by the combustion method and characterized by X-ray diffraction (XRD), Raman, UV-Vis, and scanning electron microscopy (SEM) techniques, obtaining a surface area of 3.28 m2 g−1 with cubic and well-organized crystallinity and a band gap of 4.06 eV. The experimental conditions optimized for degradation of an etoposide solution (0.4 mg L−1) were pH 5 and catalyst concentration of 1 g L−1. The results showed that the degradation processes using SrSnO3 combined with H2O2 (0.338 mol L−1) obtained total organic carbon removal from the etoposide solution, 97.98% (± 4.03 × 10−3), compared with TiO2, which obtained a mineralization rate of 72.41% (± 6.95 × 10–3). After photodegradation, the degraded solution showed no toxicity to zebrafish embryos through embryotoxicity test (OECD, 236), and no genotoxicity using comet assay and micronucleus test.
Keywords: Antineoplastic; AOPs; Comet assay; Micronucleus test; SrSnO3; Waste treatment